Effect of dilute rare-earth addition on structural evolution, mechanical, magnetic, and radiation shielding properties of CoFeNiMnTi high-entropy alloy - Ozkul, Iskender; Kalay, Ece; Guler, Omer; Karaduman, Oktay; Canbay, Canan Aksu; Hameed, Louis Ibrahim; Tekin, H. O. (Elsevier, 2026)
This study investigates the effect of 1 at.% rare-earth (RE = Sm, Gd, Dy) addition on the structural, mechanical, magnetic, and radiation shielding properties of CoFeNiMnTi high-entropy alloys produced by arc melting. X-ray diffraction results reveal an FCC-dominant structure accompanied by secondary Laves-type phases, with increased phase complexity observed in Gd-and Dy-containing alloys. Mechanical evaluation shows a significant hardness enhancement, reaching 581 HV for Gd and 548 HV for Dy, compared to 447 HV for the reference alloy. Magnetic measurements indicate soft-ferromagnetic behaviour for all compositions, with magnetization increasing in the order S0
Keywords: High-Entropy Alloys; Rare-Earth Elements; Radiation Shielding; Magnetic Properties; Mechanical Strengthening